2019
DOI: 10.2807/1560-7917.es.2019.24.48.1900604
|View full text |Cite
|
Sign up to set email alerts
|

Low 2018/19 vaccine effectiveness against influenza A(H3N2) among 15–64-year-olds in Europe: exploration by birth cohort

Abstract: Introduction: Influenza A(H3N2) clades 3C.2a and 3C.3a co-circulated in Europe in 2018/19. Immunological imprinting by first childhood influenza infection may induce future birth cohort differences in vaccine effectiveness (VE). Aim: The I-MOVE multicentre primary care test-negative study assessed 2018/19 influenza A(H3N2) VE by age and genetic subgroups to explore VE by birth cohort. Methods: We measured VE against influenza A(H3N2) and (sub)clades. We stratified VE by usual age groups (0-14, 15-64, ≥ 65-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 28 publications
8
44
0
Order By: Relevance
“…The low all-ages influenza A (H3N2) VE estimate observed in Israel, was consistent with the genetic and antigenic analysis of these viruses. In addition, it was consistent with the all-ages influenza A (H3N2) clade 3C.3a VE estimates in the USA [21], Canada [20], and Europe [22].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The low all-ages influenza A (H3N2) VE estimate observed in Israel, was consistent with the genetic and antigenic analysis of these viruses. In addition, it was consistent with the all-ages influenza A (H3N2) clade 3C.3a VE estimates in the USA [21], Canada [20], and Europe [22].…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies by Skowronski et al [20] and Kissling et al [22] demonstrated statistically significant negative 2018-2019 influenza A (H3N2) VE estimates among the age ranges of 39-53 years old [20] and 32-54 years old [22], respectively. Skowronski et al hypothesized that immune imprinting that occurred during childhood towards a common epitope of the hemagglutinin (HA) protected adults that did not receive the 2018-2019 influenza vaccine against the circulating 3C.3a influenza A (H3N2) viruses, whereas the immune response elicited by the 2018-2019 mismatched influenza A (H3N2) vaccine antigen interfered with this protection [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An immunological cohort effect (i.e. imprint-regulated effect of vaccine; I-ReV) was hypothesised last season to explain the paradoxical negative VE for the 3C.2a1 vaccine against 3C.3a viruses, notably among adults 35-54 years of age [25,28,29]. Whether the I-ReV hypothesis may also apply, but in reverse, to explain this season's protective VE for 3C.3a vaccine against 3C.2a1 viruses requires greater sample size to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by other authors have found moderate IVE in the 2018-2019 season [3,[38][39][40]. It must be pointed out, however, that the design of all the published studies was different from ours; indeed, they were case-control test-negative studies in primary care and hospital settings.…”
Section: Discussionmentioning
confidence: 68%